2017
DOI: 10.1121/1.4976047
|View full text |Cite
|
Sign up to set email alerts
|

On the localization of high-frequency, sinusoidally amplitude-modulated tones in free field

Abstract: Previous headphone experiments have shown that listeners can lateralize high-frequency sine-wave amplitude-modulated (SAM) tones based on interaural time differences in the envelope. However, when SAM tones are presented to listeners in free field or in a room, diffraction by the head or reflections from room surfaces alter the modulation percentages and change the shapes of the envelopes, potentially degrading the envelope cue. Amplitude modulation is transformed into mixed modulation. This article presents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…3 ), with comparable results observable in other HRTF databases as well (data not shown; e.g., Denk and Kollmeier, 2020 ). These findings imply that while there appears to be little discussion of non-monotonic ENV-ITD-azimuth functions in the literature (to our knowledge, only one other study has reported them; Macaulay et al, 2017 ), such non-monotonicities evidently occur and could potentially impact perception. Furthermore, they imply conventional time-independent models of binaural cue generation may fail to capture more complex and time-dependent interactions of real signals propagated around the head.…”
Section: Discussionmentioning
confidence: 75%
“…3 ), with comparable results observable in other HRTF databases as well (data not shown; e.g., Denk and Kollmeier, 2020 ). These findings imply that while there appears to be little discussion of non-monotonic ENV-ITD-azimuth functions in the literature (to our knowledge, only one other study has reported them; Macaulay et al, 2017 ), such non-monotonicities evidently occur and could potentially impact perception. Furthermore, they imply conventional time-independent models of binaural cue generation may fail to capture more complex and time-dependent interactions of real signals propagated around the head.…”
Section: Discussionmentioning
confidence: 75%
“…Interaural group delay is an additional physical cue complementing the IPDs. It is used to describe interaural cues in acoustic waveforms at the ears prior to processing by the auditory system (Macaulay et al, 2017).…”
Section: Interaural Group Delaymentioning
confidence: 99%